Efektifitas Rancangan Undang-Undang Hukum Materiil Peradilan Agama (RUU HMPA) Dalam Penanggulangan Nikah Sirri - Faisol Rizal (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2018)
The draft of Law on the Religious Courts Material Law is a draft law that is still in the stage of discourse and declaration by the authorities. This draft law has one article that is quite interesting to study, namely the law of punishment for sirri marriage. As an eastern country that still follows eastern wisdom; and Indonesian people who are Muslim, there are still many practitioners who practice sirri marriage among the people. This is due to many factors including lack of marriage registration material, less socialized marriage regulations and others. Many approaches are carried out by researchers from socialist circles, academics and historians who produce different assumptions about the problem of "reluctance to marriage records". This law is in accordance with the spirit of Islam in order to benefit. The maqashid syariah approach is an effective approach in combining positive law and shari'ah law.